EFFECT OF ETHANOLIC EXTRACT OF FRUITS OF ERIOBOTRYA JAPONICA ON LIPID PROFILE AND BODY WEIGHT IN STREPTOZOTOCIN INDUCED DIABETIC RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Eriobotrya japonica locally called as loquat in Kashmir has been studied in various parts of the world but little work has been reported on Kashmiri loquat. The chemical nature of fruits and vegetables offers a great diversity of biological properties and plays an important role in the field of pharmacology. There is a quest for newer drugs with few adverse effects and this poses a challenge for the development of new drugs. The study was undertaken to study the activities of ethanolic extract of Eriobotrya japonica fruits in streptozotocin induced diabetic rats. The phytochemical screening of the plant was also done. The animals were divided into five groups. Normal Control group received only the vehicle. Toxic group included those animals in which diabetes was induced by streptozotocin. The 3rd group was those animals which received streptozotocin and standard antidiabetic drug-glibenclamide. 4th group included those diabetic animals which received 50 mg/kg b.w dose of fruits of Eriobotrya japonica. 5th group animals included those diabetic animals which received 100 mg/kg b.w of the plant extract. The biochemical parameters that were evaluated were blood glucose levels and lipid profile tests. The body weight was also checked. Histopathology of pancreas was also done. The results showed significant decrease in blood glucose levels, lipid profile tests in animals treated with different doses of the plant extracts. Histopathology of pancreas also showed positive results.